2012
DOI: 10.1556/abiol.63.2012.suppl.2.31
|View full text |Cite
|
Sign up to set email alerts
|

Modulation ofMytilus trossulus(Bivalvia: Mollusca) larval survival and growth in culture

Abstract: Commercial importance and ability to live in a wide range of salinities have made the common mussel, Mytilus trossulus, a relevant model to study modulation of larval growth and development. We investigated the effects of various salinities combined with neomycin and ampicillin application on Mytilus larvae survival and growth. Both neomycin and ampicillin enhanced trochophore and veliger survival under condition of low salinity. The average veliger size was increasing in accordance with the increase of salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Thus, both may be involved in the regulation of locomotion, distribution, and defensive behavior. In addition, the FMRFamide peptide family modulates ligand-gated channels that transport Na + and associated water, rendering larvae resistant to osmotic pressure [29, 5962]. FMRFamide, expressed in the early peripheral neurons of bivalve and gastropod larvae [3, 14, 21, 48], has been suggested to modulate their behavior in response to environmental changes (for example, in salinity, temperature, and pH) in their ecological niche, where appropriate movement in the water column determines successful survival.…”
Section: Unsolved Questions On Lophotrochozoans Neurodevelopmentmentioning
confidence: 99%
“…Thus, both may be involved in the regulation of locomotion, distribution, and defensive behavior. In addition, the FMRFamide peptide family modulates ligand-gated channels that transport Na + and associated water, rendering larvae resistant to osmotic pressure [29, 5962]. FMRFamide, expressed in the early peripheral neurons of bivalve and gastropod larvae [3, 14, 21, 48], has been suggested to modulate their behavior in response to environmental changes (for example, in salinity, temperature, and pH) in their ecological niche, where appropriate movement in the water column determines successful survival.…”
Section: Unsolved Questions On Lophotrochozoans Neurodevelopmentmentioning
confidence: 99%
“…The marine bivalve Crenomytilus grayanus proved to be very sensitive to changes in salinity, which could block feeding and retard larval growth (Yaroslavtseva and Sergeeva, 2010). Moreover, it was shown that changes in salinity have an impact on the growth and survival of the larvae of another marine bivalve, Mytilus trossulus, influencing simultaneously the expression of 5-HT and FMRFa immunoreactivities (Vekhova et al, 2012). In the marine snail Ilyanassa obsoleta, acidic seawater was found to stimulate metamorphosis, a process also regulated by different transmitter systems, such as 5-HT, nitric oxide, and FMRFamide (Leise and Cahoon, 2012;Leise et al, 2014).…”
Section: Functional-physiological Considerationsmentioning
confidence: 99%
“…Among all other organ systems of mollusks, the nervous system and its neurotransmitters are of great importance in the regulation of homeostasis in general, and particularly in various physiological processes; such as regulation of locomotor activity [9], contraction of striated and smooth (catch) muscles including the heart [2,4], regulation of metabolism [10], circulation, feeding, digestion, reproduction, and osmoregulation [11][12][13][14][15]. In addition, the modulation of neurotransmitter expression leads to a change in the rate of larval development [16].…”
Section: Introductionmentioning
confidence: 99%